Progressive Realisation of Universal Health Coverage in Low- and Middle-Income Countries: Beyond the "Best Buys" - Melanie Y. Bertram; Jeremy A. Lauer; Karin Stenberg; Ambinintsoa H. Ralaidovy; Tessa Tan-Torres Edejer (Kerman University of Medical Sciences, 2021)
BackgroundWorld Health Organization Choosing Interventions that are Cost-Effective (WHO CHOICE) has been a programme of the WHO for 20 years. In this latest update, we present for the first time a cross programme analysis of the comparative cost-effectiveness of 479 intervention scenarios across 20 disease programmes and risk factors. MethodsThis analysis follows the standard WHO CHOICE approach to generalized cost-effectiveness analysis applied to two regions, Eastern sub-Saharan Africa and Southeast Asia. The scope of the analysis is all interventions included in programme specific WHO CHOICE analyses, using WHO treatment guidelines for major disease areas as the foundation. Costs are measured in 2010 international dollars, and benefits modelled beginning in 2010, or the nearest year for which validated data was available, both for a period of 100 years. ResultsAcross both regions included in the analysis, interventions span multiple orders of magnitude in terms of cost-effectiveness ratios. A health benefit package optimized through a value for money lens incorporates interventions responding to all of the main drivers of disease burden. Interventions delivered through first level clinical and nonclinical services represent the majority of the high impact cost-effective interventions. ConclusionCost-effectiveness is one important criterion when selecting health interventions for benefit packages to progress towards universal health coverage (UHC), but it is not the only criterion and all calculations should be adapted to the local context. To support country decision-makers, WHO CHOICE has developed a downloadable tool to support the development of data for this criterion.